The biology teacher profile of junior and senior high school and the use of learning models in Ternate Indonesia - Ilham Madjid; Aloysius Duran Corebima; Hadi Suwono; Susriyati Mahanal (University of Muhammadiyah Malang, 2024)
The implementation of instructional models in the classroom significantly impacts students’ learning abilities and achievements. The adoption of a teacher-centered learning approach might lead to reduced student engagement in the learning process, consequently influencing their ability to acquire life skills. The current study aimed to determine the educational attainment, teaching experience, utilization of learning media and application of learning models by junior and senior high school biology teachers in Ternate, Indonesia. This study employed a qualitative research method that utilized survey questionnaires. The respondents were 25 biology teachers of junior high school and 30 biology teachers of senior high school. The research findings showed that (1) 84% of the junior high school biology teachers have the undergraduate education and 16% of them have the master education; 69.77% of those of the senior high school have the undergraduate education and 30.23% of them have the master education. (2) Both the junior and the senior high school biology teachers have over 15 years of teaching experience. (3) Among the junior high school biology teachers, the use of student worksheet is only 20%, and the use of learning media is 14%; Among the senior high school biology teachers, the use of student worksheet is 36.66% and the use of learning media is 23.33%. (4) The uses of conventional learning and the use of cooperative learnings among junior high school biology teachers are 83% and 17%, respectively; where as among those of senior high school are 73.34% and 26.66%, respectively. In conclusion, the educational qualifications of junior and senior high school biology teachers in Ternate have satisfied the necessary criteria for teaching. However, the teachers have not been able to enhance the quality of education in the city. This highlights the importance of developing innovative learning models to improve the learning abilities and achievements.